2006
DOI: 10.1037/0735-7044.120.4.880
|View full text |Cite
|
Sign up to set email alerts
|

Medial auditory thalamic nuclei are necessary for eyeblink conditioning.

Abstract: The auditory conditioned stimulus (CS) pathway that is necessary for delay eyeblink conditioning was investigated with induced lesions of the medial auditory thalamus contralateral to the trained eye in rats. Rats were given unilateral lesions of the medial auditory thalamus or a control surgery followed by twenty 100-trial sessions of delay eyeblink conditioning with a tone CS and then five sessions of delay conditioning with a light CS. Rats that had complete lesions of the contralateral medial auditory thal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
54
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 61 publications
5
54
0
Order By: Relevance
“…The CB1Rs are very dense in the hippocampus and disrupting hippocampal activity can impair delay conditioning (Solomon et al 1983). Disruption of auditory system function could also impair acquisition as well (Halverson and Freeman 2006). Low levels of CB1Rs are found in the red nucleus (Herkenham et al 1991), but alterations in magnocellular neuronal function could impair CR performance by affecting excitatory input to the facial motor nucleus, which produces the blink response (Trigo et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The CB1Rs are very dense in the hippocampus and disrupting hippocampal activity can impair delay conditioning (Solomon et al 1983). Disruption of auditory system function could also impair acquisition as well (Halverson and Freeman 2006). Low levels of CB1Rs are found in the red nucleus (Herkenham et al 1991), but alterations in magnocellular neuronal function could impair CR performance by affecting excitatory input to the facial motor nucleus, which produces the blink response (Trigo et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies using lesions, inactivation, stimulation, and neural tract tracing have provided evidence that the auditory CS pathway that is necessary for acquisition and retention of eyeblink conditioning is comprised of converging inputs to the medial auditory thalamic nuclei (MATN), and a direct ipsilateral projection from the MATN to the PN (Halverson and Freeman 2006;Campolattaro et al 2007;Freeman et al 2007;Halverson et al 2008). Unilateral lesions of the MATN, contralateral to the conditioned eye, block acquisition of eyeblink CRs to a tone CS but have no effect on conditioning with a light CS (Halverson and Freeman 2006).…”
mentioning
confidence: 99%
“…Notably, no activity was detected in either the LGN or superior colliculus at any stage during these experiments, although a number of previous studies have demonstrated a role for the subcortical structures of the sensory systems in classical conditioning. Lesions of the auditory (LeDoux et al, 1986;Halverson and Freeman, 2006) and visual (Koutaldis et al, 1988) thalamic nuclei have been shown to inhibit classical conditioning. Electrophysiological recordings have demonstrated that classical conditioning induces retuning of the auditory thalamic nuclei (Edeline and Weinberger, 1992).…”
Section: Discussionmentioning
confidence: 99%